Understanding the Curricular Needs and Practice Contexts of Macro Social Work: A Community-Based Process. (2nd July 2020) - Sousa, Cindy A.; Yutzy, Lemuel; Campbell, Margo; Cook, Casey; Slates, Sarah
ABSTRACT: Macro social workers have consistently taken up the difficult task of articulating and refining our identity. Deciding on priorities for the preparation of students is a key component of this work. Standards and areas of focus set by our accrediting and organizing bodies (Council on Social Work Education [CSWE], Association for Community Organization and Social Administration [ACOSA]) are a great help toward this goal of continual refinement of standards and competencies for macro practice. Adding to this scholarship, our research uses practitioner interviews from a large, urban area ( N = 16); our research goal was to examine the essential knowledge, skills, and attributes for macro social workers and to determine associated programmatic considerations. Findings highlight the need to honor and promote the unique disciplinary framework and philosophical underpinnings of macro social work, while also preparing students to work across multiple levels of practice and diverse disciplines.